Floods, Gravelly grounds, Islands of the Po river in the Early Modern Age. A case-study about Parma and Cremona during the XVI century (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Floods and other water disasters always modified not only the fluvial landscape, but also the relationships among the social and political actors of a determinated land. Without ambitions of completeness, the paper aims to analyze a case‐study regarding the provinces of Cremona and Parma during the early modern age to show which kind of claims and juridical solutions used to be more frequent. The focus will be particularly on a juridical dispute rosen during the year 1546 because of some properties along the Po river: it was a political problem because the floods were modifying lands at the borders between the Dukedom of Milan, under the control of Charles V, and the new born dukedom of Parma and Piacenza.
Keywords: Floods; jurisdictions; Po River; Duchy of Parma and Piacenza; Duchy of Milan